Natural deep eutectic solvents vs. conventional solvents: effects on crude yield, mangiferin content, antioxidant activity, and toxicity in Mangifera pajang Kosterm. fruit extracts - Muhammad Daniel Eazzat Mohd Rosdan,; Mohd Azrie Awang,; Mohammad Amil Zulhilmi Benjamin,; Fritzgerald Andrew,; Aniza Saini,; Siti Faridah Mohd Amin,; Norliza Julmohammad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Mangifera pajang Kosterm. fruits, commonly known as 'Bambangan,' are rich in natural antioxidants due to their phytochemical constituents and are categorised as an underutilised fruit. This study focused on investigating the effects of different solvents on the extraction yield (EY), mangiferin content (MC), total flavonoids (TF), total phenolics (TP), antioxidant activity, and toxicity of M. pajang fruit extracts (MPFE). The selected solvents included natural deep eutectic solvents (NADES), water, methanol, and ethanol. The extraction of MPFE was performed using ultrasound-assisted extraction with an ultrasonic probe. Antioxidant activities were evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and ferric-reducing antioxidant power (FRAP) assays. Toxicological assessment was conducted using the brine shrimp lethality assay (BSLA) to determine LC50 values. Overall, NADES proved to be the most efficient solvent for extraction, yielding the highest EY (37.09 ± 2.34%), MC (0.032 ± 0.000 mg/g), TF (0.80 ± 0.01 mg RE/g dry extract), TP (14.94 ± 1.74 mg GAE/g dry extract), and exhibits potent antioxidant activity as measured by DPPH (82.38 ± 0.24%), ABTS (86.37 ± 0.03%), and FRAP (304.57 ± 5.24 mg TE/g dry extract). Moreover, NADES demonstrated non-toxicity in the BSLA (LC50 = 1988.37 μg/mL) of MPFE. These findings suggest that NADES is a suitable solvent for exploring the medicinal potential of M. pajang fruits and their application in therapeutic development.